2017
DOI: 10.17576/jsm-2017-4602-09
|View full text |Cite
|
Sign up to set email alerts
|

Mood, Cognitive Function and Quality of Life Improvements in Middle Aged Women Following Supplementation with Polygonum minus Extract

Abstract: Polygonum minus is a plant rich in flavonoids and antioxidants beneficial for reducing oxidative stress and lipid peroxidation in neuronal membranes. This randomized, double-blind, placebo-controlled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Significant improvements were observed in most of the negative mood status particularly tension, anger, confusion, and total negative subscales in the present study. Our findings were in line with the previous study [ 27 ], which also demonstrated significant improvements in tension, depression, anger, and total mood disturbance among healthy middle-aged women with mood disturbance. Quercetin and Q3G have been suggested to have an anti-depression ability [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Significant improvements were observed in most of the negative mood status particularly tension, anger, confusion, and total negative subscales in the present study. Our findings were in line with the previous study [ 27 ], which also demonstrated significant improvements in tension, depression, anger, and total mood disturbance among healthy middle-aged women with mood disturbance. Quercetin and Q3G have been suggested to have an anti-depression ability [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…A previous study using a similar P. minor supplement (previously known as LineMinus™) (500 mg/day) also reported significant improvements in Digit Span, Comprehensive Trail Making Test, and CNS vital signs in cognitive flexibility and executive function among healthy middle-aged women after 6 weeks of consumption [ 27 ]. Together with the current finding, both short and long duration consumption of P. minor extract supplement has the potential to improve cognitive domains such as attention, cognitive flexibility and executive function among middle-aged adults and visual memory among older adults with MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing capsule to placebo, the data showed a significant decrease in mood, angerand tension among capsule supplemented subjects (Udani 2013). The study by Shahar et al (2015) reported that supplementation of two Polygonum minus (kesum) capsules (250 mg) taken once daily has the potential to improve mood and quality of life after 6 weeks of intervention compared to baseline among 35 to 55 years old middle-aged women (Shahar et al 2015;Yahya et al 2017). This result was supported by George et al (2014) study which reported that Polygonum minus possesses antioxidant and anticholinesterase activity and demonstrated enhanced cognition in vivo.…”
Section: Role Of Polyphenols In Improving Cognitive Declinementioning
confidence: 99%
“… This traditional dish was not only found to have contained a high level of antioxidants, the polyphenol in the ulam was also reported in a review as attenuating the oxidative stress that consequently prevents cognitive decline . Although the neuropsychological batteries (ie, Mini‐mental State Examination, Digit Span, General Health Questionnaire) had been used for measuring the respective benefits of Polygonum minus supplements as well as the Centella asiatica and Oenanthe javanica for improving the attention and memory among middle‐aged women and the cognitive impairment associated with the neurodegenerative disorders such as Alzheimer's disease and dementia; however, brain activation using fMRI is yet to be investigated . As such, the fMRI technique is therefore recommended to assess the working memory performance and cognitive flexibility based on brain activation that is located at the dorsolateral prefrontal cortex of the subjects.…”
mentioning
confidence: 99%